TEACHER PERFORMANCE ECONOMIC DIFFERENCE IN LEVEL BETWEEN STATE junior CERTIFICATION WITH THAT WHICH HAS NOT BEEN AND CERTIFICATION IN DISTRICT shadows KOTO IN THE DISTRICT XI Tarusan - febrina, Yesi - (Pendidikan Ekonomi, 2014)
The subject is examined in this study is how the relationship pedagogical ability, personality,social and professional towards economics teacher performance differences that have been certifiedand are not yet certified. This research was conducted at the level of Junior High School in DistrictDistrict of Bayang and Koto XI Tarusan economy where the population is teachers who are alreadycertified and who have not been certified, and the sampling technique using total sampling. Data werecollected through a questionnaire or a questionnaire. Data were analyzed by chi-square analysismethods.The results showed that: In hypothesis testing chi square analysis results showed chi-squarevalue of 415.508 with a p-value 0.073 value. Since the value of p-value 0.073> 0.05 means that thereis no difference between teacher certification with the performance of non-certified teachers. Rank ofthe output can be seen that the mean value for non-certified teachers (0) is smaller than the value ofteacher certification (33.25 <41.88). From Mann_Whitney U test analysis can be seen in the output of"Test Statistics" where the value of the test statistic Z is small at -1.693 and sig 2-tailed value is 0.090>0.05. Because the test results are not statistically significant. Thus, H0 is accepted that there is nodifference in the performance of teachers certified by the non-certification.The implication of this study is To the Economics teacher in junior high who has thecertification that is expected to not only meet the teaching hours 24 hours a week, but in the suggestfurther improve the performance of their competence in the learning process and keep raising the barin the learning process, as in the preparation of learning , implementation of learning, learningevaluation, and follow-up as well as mastery of the material and increase knowledge.